Design and feasibility study of novel paraboloid graphite based microbial fuel cell for bioelectrogenesis and pharmaceutical wastewater treatment. Issue 1 (February 2021) - Rashid, Tazien; Sher, Farooq; Hazafa, Abu; Hashmi, Rizwan Qureshi; Zafar, Ayesha; Rasheed, Tahir; Hussain, Sadiq
Graphical abstract: Highlights: A novel paraboloid graphite based MFC was built for PIW treatment and bioelectrogenesis. MSW was used as a substrate for the development of biofilm and biocatalyst. Maximum power and current densities achieved were as 2.01 W/m 3 and 168 mA/m 2 . Maximum COD and TDS removal for PIW were attained as 80.55 and 35.62%. Membrane-less MFC showed feasibility for PIW treatment and bioelectrogenesis. Abstract: The raising pharmaceutical industrial wastewater (PIW) is one of the major health problems nowadays, not only for aquatic life but also for human beings and the environment. Several conventional techniques including coagulation, filtration, biological membranes and advanced oxidation have been used for the treatment of PIW, however, all of these techniques are limited with their applications and results. The present study aimed to build a cost-effective, high biodegradable, eco-friendly and highly efficient PIW treatment technique to generate electricity and reduce the COD of wastewater simultaneously. A novel paraboloid shaped graphite-based microbial fuel cell (MFC) configuration has been designed by eliminating different types of casings and membranes for bio-electrogenesis and treatment of PIW. Municipal solid wastewater (MSW) was used as a substrate for developing the biofilm in paraboloid graphite-based MFC. The PIW treatment showed adequate bioelectricity generation including; current, power, voltage and open-circuit voltage (OCV) of about 2.76 mA, 0.76 mW, 276 mV and 330 mV at 100 Ω respectively after five operating cycles. The cyclic voltammetry showed the maximum generation of 2.01 W/m 3 and 168 mA/m 2 of power and current densities respectively followed by a considerable reduction in internal resistance from 197 to 99 Ω. The results reported a significant amount of reduction in COD (80.55%) and TDS (35.62%) for PIW by MFC respectively. The reduction in the percentage removal efficiency of COD (80.55%) suggested that the removal of organic compounds from PIW is parallel to bioelectrogenesis. Based on these major findings the novel membrane-less and paraboloid graphite-based MFC operation significantly drag concentration towards the feasibility of using pharmaceutical wastewaters for bio-electrogenesis.